Building Loyalty Amid Café Competition: The Role of Experiential Marketing through Customer Engagement, Self-Expression Value, and Hedonic Value in Cafés in Jambi - Andri Yandi; Hapzi (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the effect of experiential marketing on customer loyalty through customer engagement, self-expression value, and hedonic value at cafés in Jambi. The study is motivated by the rapid growth of cafés and coffee shops in Jambi City, which has intensified business competition. This research employed a quantitative approach using a survey method. The population of this study consisted of café customers in Jambi City, with a total sample of 135 respondents. The data analysis technique used was Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that experiential marketing has a positive and significant effect on customer engagement, self-expression value, hedonic value, and customer loyalty at cafés in Jambi City. Furthermore, customer engagement does not have a significant effect on customer loyalty. Meanwhile, self-expression value and hedonic value were found to have a positive and significant effect on customer loyalty. Therefore, customer loyalty at cafés in Jambi City is more strongly influenced by emotional experiences, enjoyment, and the alignment between customers’ lifestyles and the café concept.